2022
DOI: 10.1038/s41598-022-24053-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D supplementation and COVID-19 infection and mortality

Abstract: Vitamin D deficiency has long been associated with reduced immune function that can lead to viral infection. Several studies have shown that Vitamin D deficiency is associated with increases the risk of infection with COVID-19. However, it is unknown if treatment with Vitamin D can reduce the associated risk of COVID-19 infection, which is the focus of this study. In the population of US veterans, we show that Vitamin D2 and D3 fills were associated with reductions in COVID-19 infection of 28% and 20%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…For this reason, vitamin D supplementation was given to elderly patients in France who were infected with COVID-19 and were less likely to exhibit the complications of the infection [ 53 ]. Vitamin D was also shown to be associated with reductions in Covid-19 infection in the population of US veterans [ 54 ]. Calcium was the most consumed mineral supplement in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, vitamin D supplementation was given to elderly patients in France who were infected with COVID-19 and were less likely to exhibit the complications of the infection [ 53 ]. Vitamin D was also shown to be associated with reductions in Covid-19 infection in the population of US veterans [ 54 ]. Calcium was the most consumed mineral supplement in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Gibbons et al has shown that the supplementation of vitamin D2 and D3 reduced the risk for COVID-19 infection, as well as mortality. The benefits were even better in people receiving higher dosages, as well as in those with a more severe deficiency ( 49 ).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Clinical findings assessed the role of vitamin D2 and vitamin D3 supplementation and showed significantly reduced risk of COVID-19 infection and death within 30 days. Therefore, the researchers believe vitamin D3 supplementation could be a valuable strategy for limiting the spread of COVID-19 infection and related death and racial differences in COVID-19 outcomes [ 132 ].…”
Section: Future Directionsmentioning
confidence: 99%